Uncovering the Protective Mechanism of the Volatile Oil of Acorus tatarinowii against Acute Myocardial Ischemia Injury Using Network Pharmacology and Experimental Validation. (22nd June 2021) - Zang, Zhen-Zhong; Chen, Li-Mei; Liu, Yuan; Guan, Yong-Mei; Du, Qing; Xu, Pan; Shen, Qian; Yang, Ming; Liu, Hong-Ning; Liao, Zheng-Gen
Abstract : Acorus tatarinowii is a traditional aromatic resuscitation drug that can be clinically used to prevent cardiovascular diseases. The volatile oil of Acorus tatarinowii (VOA) possesses important medicinal properties, including protection against acute myocardial ischemia (MI) injury. However, the pharmacodynamic material basis and molecular mechanisms underlying this protective effect remain unclear. Using network pharmacology and animal experiments, we studied the mechanisms and pathways implicated in the activity of VOA against acute MI injury. First, VOA was extracted from three batches of Acorus tatarinowii using steam distillation, and then, its chemical composition was determined by GC-MS. Next, the components-targets and protein-protein interaction networks were constructed using systematic network pharmacology. Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were also conducted in order to predict the possible pharmacodynamic mechanisms. Furthermore, animal experiments including ELISAs, histological examinations, and Western blots were performed in order to validate the pharmacological effects of VOA. In total, 33 chemical components were identified in VOA, and ß -asarone was found to be the most abundant component. Based on network pharmacology analysis, the therapeutic effects of VOA against myocardial ischemia might be mediated by signaling pathways involving COX-2, PPAR- α, VEGF, and cAMP. Overall, the obtained results indicate that VOA alleviates the pathological manifestations of isoproterenol-hydrochloride-induced myocardial ischemia in rats, including the decreased SOD (superoxide dismutase) content and increased LDH (lactic dehydrogenase) content. Moreover, the anti-MI effect of VOA might be attributed to the downregulation of the COX-2 protein that inhibits apoptosis, the upregulation of the PPAR- α protein that regulates energy metabolism, and the activation of VEGF and cAMP signaling pathways.